Hermafroditismo verdadeiro na espécie canina - Costa, Paula Priscila Correia; Filho, Cleyson Teófilo Braga; Freitas, Luana Azevedo; dos Santos, Maressa Holanda; Cabral, Leonardo Alves Rodrigues; Silveira, João Alison de Morais; de Araújo, Airton Alencar (Acta Scientiae Veterinariae, 2017)
Background: Hermaphroditism or intersex is a general term that includes various congenital anomalies of the genital system which is used to define animals with ambiguous sexual characteristics. It occurs in domestic animals, more commonly in pigs and goats, and rarely in horses, dogs, sheep, and cattle. The prevalence of hermaphroditism varies a lot among breeds and species and is higher in groups with a high degree of consanguinity. Therefore, the objective of this report is to describe a case of canine hermaphroditism in a dog with male phenotype, as well as the anatomical and hormonal findings, and classification of the hermaphroditism exhibited by the animal studied. Case: A 1-year-old, mongrel, 5 kg dog was referred to the UHV-UECE due to the presence of a slit on the lower quadrant of the abdomen, caudal to the umbilical scar. At examination, the animal exhibited normal rectal temperature, no alterations of palpable lymph nodes, and a satisfactory body condition score. The pubic area had 2 testicles, each one in a different scrotum, 1 to the right and 1 to the left of the slit. A prepuce with no apparent function was present cranially to the slit, closer to the umbilical scar. At the other extremity of the slit, on the pubic region, there was a flaccid structure similar to a penis (micropenis) with no penile bone and no function. The slit was open until the area ventral to the anus, where the urethra was detected. The animal exhibited a behavior of territory demarcation with urine typically seen in male dogs. Orchiectomy and slit correction surgery were performed. Pre-surgical exams included: complete blood count and hormonal doses of estradiol, testosterone, and progesterone. Abdominal ultrasound was performed to assess presence of sexual glands and gonads. The hormonal exam revealed: estradiol 56.39 pg/mL; testosterone 127.9 ng/mL; progesterone 0.892 ng/mL. A uterus was not detected on ultrasound examination. Ovaries were seen on their typical anatomical position; they were symmetrical and had normal sizes. There was a normal size prostate in the pelvic area, exhibiting normal texture and echogenicity. No other abnormalities were seen and the owner opted for no further surgical intervention. Discussion: Testosterone predominance explains the male behavior and appearance, demonstrating that the testis were prevalent over the ovaries. The occurrence of XX males has been reported. The genetic cause is the absence of the SRY chromosome, which has a fundamental role on activation of the SOX gene, which is responsible for sex determination. Clinically, a true hermaphrodite can exhibit different degrees of genital ambiguity; they can be diagnosed during puberty with the emergence of heterosexual characteristics, or as an adult, with infertility or gonadal neoplasia. True hermaphrodites are individuals with testicular and ovarian tissues, either combined in one gonad (ovotestis) or present as two separate gonads. The presence of ovaries and testicles can be confirmed by histology, which was not performed in this study. However, ultrasound findings (prostate and ovaries), and the presence of normal testis and external genitalia without a defined penis or vulva are in accordance with the description of a true hermaphrodite.